Investigating Meat Milling Business in Yogyakarta: a Maqâshid al-Syarî‘ah Perspectives - Muttaqin, Zein; Ferdaus, Nadia Nuril (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2017)
Investigating Meat Milling Business in Yogyakarta: A Maqâshid al-Syarî‘ah Perspectives. This article aims to investigate the meat milling business process in the light of maqâshid al-syarî‘ah perspectives. The ttopic arises due to some past cases related to the mixed process of meat milling of lawful and unlawful meat in the industry, while the demand on the meat milling business is pretty high according to the BAPPENAS Yogyakarta data. Lacking on supervision has threatened consumer protection and deviates from the sharia injunctions. Maqâshid al-syarî‘ah being consider as the basis of sharia compliances that serves to understand the purposes of sharia laws in the daily life in the form of prohibitions and injunctions. Qualitative method and content analysis is conducted to interpret 7 meats milling local shop owner responds regards the manifestation of maqâshid al-syarî‘ah in their business. It can be concluded that the implementation of maqâshid al-syarî‘ah of meat milling business in Yogyakarta on the level of input, process and output has been implemented accordingly. Although there are several cases of respondent that did not abide by the Islamic laws, but most of the businessman are. Halal logistic and supply chain is needed to become the insurance party of the legal aspect of business and also as the milestone of expanding the local meat milling to compete with the bigger competitor such as supermarket.